The Influence of Work Environment, Work Facilities, and Job Satisfaction on Employee Performance at PT. Adam Dani - Nabilla Zein; Yohny Anwar (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This research was conducted on PT. Adam Dani Lestari with the aim of research to know and analyze the influence of the work environment, work facilities, and partial and simultaneous seara job satisfaction on the performance of employees in performing tasks. The population is employees who work in the company as many as 85 people and sampling with saturated samples with 85 respondents. The type of data is used i.e. primary data and data sources are used i.e. secondary data, data collection techniques using library studies, surveys and observations. Data analysis techniques are multiple linear regression, classic assumption test and hypothesis test. The results of the study that the work environment, work facilities and job satisfaction partially and simultaneously positive and significant employee performance. There is a very strong correlation between the work environment, work facilities and job satisfaction with the performance of employees in performing tasks in the company. R2 = 0.844 means that the performance of employees in the company can be explained by the work environment, work facilities and job satisfaction of 84.40% and the remaining 15.6% can be explained by other variables that are not researched.